Notable postnatal alterations in the myenteric plexus of normal human bowel. Issue 5 (1st May 1999) - Wester, T; O'Briain, D S; Puri, P
Abstract : BACKGROUND: Nitric oxide is the most important transmitter in non-adrenergic non-cholinergic nerves in the human gastrointestinal tract. Impaired nitrergic innervation has been described in Hirschsprung's disease, hypertrophic pyloric stenosis, and intestinal neuronal dysplasia (IND). Recent findings indicate that hyperganglionosis, one of the major criteria of IND, is age dependent. However, information is scanty regarding the neurone density in normal human bowel in the paediatric age group. AIMS: To determine neurone density, morphology, and nitric oxide synthase distribution of the normal myenteric plexus at different ages during infancy and childhood. METHODS: Specimens were obtained from small bowel and colon in 20 children, aged one day to 15 years, at postmortem examination. Whole mount preparations were made of the myenteric plexus, which were subsequently stained using NADPH diaphorase histochemistry (identical to nitric oxide synthase) and cuprolinic blue (a general neuronal marker). The morphology of the myenteric plexus was described and the neurone density estimated. RESULTS: The myenteric plexus meshwork becomes less dense during the first years of life. The density of ganglion cells in the myenteric plexus decreases significantly with age during the first three to four years of life. The NADPH diaphorase positive (nitrergic) subpopulation represents about 34% of all neurones in the myenteric plexus. CONCLUSIONS: The notable decrease in neurone density in the myenteric plexus during the first years of life indicates that development is still an ongoing process in the postnatal enteric nervous system. Applied to the clinical situation, this implies that interpretation of enteric nervous system pathology is dependent on the age of the patient.